19F Dynamic Nuclear Polarisation: Towards a novel method for studies of protein dynamics - Gennaro, Antonio (2019)
Nuclear Magnetic Resonance (NMR) spectroscopy is a powerful technique capable of reporting on the structure of molecules and has numerous applications in chemistry, biophysics and medicine. It is based on probing transitions between energy levels formed by non-zero spins placed in a static magnetic field. Nuclei of 19F, due to their high natural abundance and large gyromagnetic ratio, are perfectly suitable for NMR spectroscopy, and they can be used for studying structure and dynamics of large and small biomolecules. However, one of the NMR significant limitations is a relatively low sensitivity, that entails the need of large amounts of studied material, or the averaging of many experimental results, that compromises the time resolution of the experiment. For example, typical solution NMR samples require few millimolars of measured substance in 2 − 3 ml volume, which is a rather large amount of material. However, in many practical cases the amount available is much lower than that. In particular, in ligand binding experiments and studies of enzymatic reactions and other kinetic processes, tracking molecules at micromolar concentration could be required. For these reasons, significant efforts in the magnetic resonance community are directed towards solving this problem of sensitivity. One of the approaches for increasing NMR signals is to use Dynamic Nuclear Polarisation (DNP), which is a process of transferring large polarisation of electron spins onto nearby nuclei via irradiation of electron energy transitions. Such a process is usually most effective at cryogenic temperatures, while NMR is most informative at ambient temperatures in solution. In their seminal work, Ardenkjaer-Larsen et al. have demonstrated that after polarisation of nuclei at low temperatures the sample can be dissolved and measured in a conventional NMR system at room temperature. This approach leads to a rapid development of such dissolution DNP systems primarily targeted towards studies of metabolites in living organisms, but also for studies of enzymatic and chemical reaction kinetics. The overarching goal of this work is to develop a methodology for studies of protein folding kinetics using dissolution DNP when protein 19F labels are added to the 19F-containing labels have previously been widely used for reporting on protein folding. The big advantages in using fluorinated compounds is the large 19F chemical shift dispersion, that leads to well-resolved peaks in the NMR spectra. Moreover, the absence of 19F background signals offers “clean” spectra compared to the ones obtained by observing at other nuclei like 1H or 13C. However, it remains difficult to perform dissolution DNP on 19F due to its short longitudinal relaxation time constant. In conventional dissolution DNP setups, the hyperpolarisation achieved would be lost between the dissolution and NMR acquisition processes, as the dead time in between these two processes is usually longer than the 19F relaxation time. However, the dual iso-centre magnet at the University of Nottingham features a short dead time of 300 ms between the dissolution and sample transferring for NMR measurements. Such a short dead time opens an opportunity to explore the fast kinetic processes such as ligand binding and protein folding kinetics, allowing to acquire the hyperpolarised 19F NMR signal before it relaxes to thermal equilibrium. Chapter 1 of this work presents an introduction to NMR spectroscopy, and the behaviour of spin 1/2 nuclei in presence of a static magnetic field is shown. An introduction to 19F NMR is also provided, showing what the main issues related to its sensitivity are, and how they can be overcame by means of dissolution DNP. In Chapter 2 magnetic resonance relaxation is discussed, explaining why a perturbed spin ensemble in a magnetic field recovers its equilibrium status. Moreover, the main mechanisms responsible for relaxation are shown. The theory of these mechanisms is needed to understand some of the issues discussed in Chapters 5 and 6. Chapter 3 presents the theory of DNP, and the main mechanisms that allow the polarisation transfer from electrons to nuclei are discussed, while in Chapter 4 brief introductions to the hardware and methodologies used for the experiments shown in this work are given. The spectrometers used for solid-state studies are presented, as well as the dual iso-centre magnet used for the dissolution DNP experiments. The main pulse sequences used to acquire the NMR spectra are also shown. In Chapter 5, the feasibility of producing large 19F polarisation at cryogenic temperatures by means of DNP is investigated in order to optimise the DNP enhancement and to establish the optimal conditions and parameters which lead to the maximum enhancement of the 19F NMR signal. For these experiments, the free radical TEMPO has been used. In addition, a spontaneous polarisation transfer from hyperpolarised 1H nuclei to 19F under solid-state DNP conditions is observed and characterised. The experiments presented in this Chapter show the importance of the electrons in the transfer process. In Chapter 6 the previously observed spontaneous polarisation transfer from 1H nuclei to 19F is studied in more detail. The free radical BDPA has been used in place of TEMPO to better understand the mechanisms that lead to this polarisation transfer. Results of DNP experiments are also shown where, alongside with the Solid Effect, a second DNP mechanism contributing for to the hyperpolarisation of 1H and 19F is observed. A quantum dynamical model is introduced to explain these results, and simulations are performed to validate the model. Chapter 7 presents the conclusions of this work, where a methodology for studies of protein folding kinetics using dissolution DNP is developed. First, the longitudinal relaxation time constants of 19F containing compounds at room temperature are investigated, to show that 19F nuclei can retain the hyperpolarisation achieved through DNP during the dead time before the NMR acquisition in a dissolution DNP experiment. Later in this Chapter, solid-state experiments are performed on simple fluorinated molecules, to optimise the 19F polarisation achieved through DNP. Finally, dissolution DNP experiments are performed on simple 19F-containing chemicals and, as a proof-of-principle, a dissolution DNP experiment is performed on a sample containing a fluorinated protein.